Consumer behavior in the intentions to change between electricity suppliers in Portugal: A push-pull-mooring framework - Vieira, F.; Meireles, M.; Trindade, G. (5th International Conference on Energy and Environment: Bringing together Engineering and Economics, 2022)
The liberalization process of the Portuguese electricity market, which started in the 1990s, is integrated in the strategic action enacted by the European Union (EU). With the introduction of competition in the electricity sector, it became essential for electricity providers to identify which factors determine consumers' choice and switching between electricity suppliers. This study intends to apply the push-pull-mooring migration theory to consumers in the electricity market to understand the switching behavior between suppliers. The results showed that push and mooring dimensions have a significant impact on consumer switching intention. In general, low satisfaction and higher value-billing of the other services can push consumers away from their current electricity supplier. Furthermore, these results suggest that the moderating effects such as the switching costs, the previous experience in this market as well as the social influence play important roles in the relationship between some components of the push effects (commitment, satisfaction, and value-billing other services) and the intention to change. Therefore, this study helps both market players and public policy makers designing strategies and incentives aligned with consumer behavior, considering both economic and psychological factors and their combined effect in their switching intention.